KEMAMPUAN SISWA KELAS VII.D SMP NEGERI 6 GUNUNG TALANG DALAM MENULIS PUISI DENGAN TEKNIK PEMODELAN; PENELITIAN TINDAKAN KELAS - Rita Arianti (STKIP ROKANIA, 2017)
The purpose of research is to describe: (1) Intensifying the process of poetry writing skills of students ,(2) the result of an increase in student poetry writing skillsstudent in class VII.D SMP Negeri 6 Gunung Talang. Data was obtained from qualitative data in the form of sheets observation, field note, questionnaires, andquantitative data in the form of test performanc. The findings of a study of the process of poetry writing skills through technigue modelling student in class VII.DSMP Negeri 6 Gunung Talang. The average student test results has increased, averaging at 46,1 pracycle, in the first cycle 59,4 and the second cycle 74,5.